Забезпечення високої результативності державної політики антикризового розвитку реального сектору економіки - Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna (My University, 2019)
UK: Стаття присвячена актуальним питанням покращення результативності державної антикризової політики реального сектору економіки. Дослідження полягає в обґрунтуванні та теоретичному осмисленні шляхів формування, методів покращення міжгалузевих технологічних взаємозв’язків як елементу розвитку реального сектору економіки. Виявлено вплив третього та четвертого технологічних укладів на функціонування національної економіки. Запропоновано шляхи покращення міжгалузевих технологічних взаємозв’язків шляхом модернізаційних процесів. Доведено, що складові модернізаційного потенціалу антикризової стратегії орієнтовані на ліквідацію наслідків економічної кризи, підвищення зайнятості населення на основі створення нових робочих місць, визначення локомотивів зростання, які спрямовані на майбутнє. RU: Статья посвящена актуальным вопросам улучшения результативности государственной антикризисной политики реального сектора экономики. Исследования заключается в обосновании и теоретическом осмыслении путей формирования, методов улучшения межотраслевых технологических взаимосвязей как элемента развития реального сектора экономики. Выявлено влияние третьего и четвертого технологических укладов на функционирование национальной экономики. Предложены пути улучшения межотраслевых технологических взаимосвязей путем модернизационных процессов. Доказано, что составляющие модернизационного потенциала антикризисной стратегии ориентированы на ликвидацию последствий экономического кризиса, повышение занятости населения на основе создания новых рабочих мест, определение локомотивов роста, которые направлены на будущее. EN: The article is devoted to actual issues of improving the effectiveness of the state anti-crisis policy of the real economy. The research consists in substantiation and theoretical understanding the ways of formation, methods of improvement of interdisciplinary technological interconnections as an element of the real sector economy development. The influence of the third and fourth technological paradigm on the functioning of the national economy is revealed. The ways of improvement of inter branch technological interconnections through modernization processes are offered. It is proved that the components of the modernization potential of the anti-crisis strategy are aimed at eliminating the consequences of the economic crisis, increasing the employment of the population through the creation of new jobs and, at the same time, aimed at identifying future growth-oriented locomotives. In today’s conditions, the constant growth and spread of processes of globalization and threats to the functioning of the national economic system, formed the following directions of anti-crisis measures in the context of the components of new growth locomotives, namely, strengthening the competitiveness of the world market through killer application, ensuring the potential for future growth through the development of basic source technologies, training of professionals staff behind the branches of the new locomotives of growth: provision of financial aid in strengthening the medium and long-term training base of personnel, identifying needs in new staff; assistance in the creation of professional Magistracy in the branches of new growth locomotives and the preparation of Masters and PhD. Evidence of the effectiveness of the introduction of crisis-management measures in the real economy is the achievement of economic growth, which is accompanied by the development of the export-oriented manufacturing sphere, the knowledge industry, and the creation of jobs.
Обеспечение высокой результативности государственной политики антикризисного развития реального сектора экономики
Providing a high result of the state policy of anti-crisis development of the real economic sector
Keywords: ринкова економіка; технологічний уклад; державна політика; науково-технічний прогрес; технологія; рыночная экономика; технологический уклад; государственная политика; научно-технический прогресс; технология; market economy; technological mode; state policy; scientific and technological progress; technology